Ballodiolic Acid A and B: Two New ROS, (•OH), (ONOO−) Scavenging and Potent Antimicrobial Constituents Isolated from Ballota pseudodictamnus (L.) Benth. - Fozia; Asmat Shaheen; Ijaz Ahmad; Syed Badar Amin; Nisar Ahmad; Riaz Ullah; Ahmed Bari; Muhammad Sohaib; Mahmood Hafiz Majid; Abdulrahman Alobaid (MDPI AG, 2021)
Bioassays guided phytochemical investigations on the ethyl acetate-soluble fraction of the root material of Ballota pseudodictamnus (L.) Benth. led to the isolation of two new compounds, ballodiolic acid A (1) and ballodiolic acid B (2), along with three known compounds ballodiolic acid (3), ballotenic acid (4), and β-amyrin (5), which were also isolated for the first time from this species by using multiple chromatographic techniques. The structures of the compounds (1-5) were determined by modern spectroscopic analysis including 1D and 2D NMR techniques and chemical studies. In three separate experiments, the isolated compounds (1-5) demonstrated potent antioxidant scavenging activity, with IC50 values ranging from 07.22-34.10 μM in the hydroxyl radical (•OH) inhibitory activity test, 58.10-148.55 μM in the total ROS (reactive oxygen species) inhibitory activity test, and 6.23-69.01 μM in the peroxynitrite (ONOO−) scavenging activity test. With IC50 values of (07.22 ± 0.03, 58.10 ± 0.07, 6.23 ± 0.04 μM) for •OH, total ROS, and scavenge ONOO−, respectively, ballodiolic acid B (2) showed the highest scavenging ability. Antibacterial and antifungal behaviors were also exposed to the pure compounds 1-5. In contrast to compounds 4 and 5, compounds 1-3 were active against all bacterial strains studied, with a good zone of inhibition proving these as a potent antibacterial agent. Similarly, compared to compounds 3-5, compounds 1 and 2 with a 47 percent and 45 percent respective inhibition zone were found to be more active against tested fungal strains.